The Portrait of the Speech of a Political Leader: new Approaches Based on Discourse Analysis / Review of the Category lnventory - Uchmanova-Shmygova, Irina (Respectus Philologicus, 2002)
The article opens a discussion about broader and deeper techniques for discourse analysis taking into consideration the interdisciplinary trend and suggesting an integrated programme for the analysis of a political discourse characteristic of a political leader. The programme is designed as a model for the text analysis of social documents and based on the causal-genetic theory developed by the author.